The Influence of Sales Promotion on Purchasing Decisions At Mini Markets in The Gayo Lues District Community - Bambang (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
This study aims to analyze the influence of promotion on purchasing decisions in choosing a place to eat in Makmur Swalayan Blangkejeren, both partially and simultaneously. Using an associative method, this study involved 100 respondents as a sample, and data were collected through questionnaires. The analysis technique used is multiple linear regression. The results of the study show that promotion has a positive and significant influence on purchase decisions. Simultaneously, promotions have a positive and significant effect on customer decisions, as shown by the value of Fcal 41.433 greater than Ftable 3.94